Living with heritage : the case of Tsodilo World Heritage Site and neighbouring localities - Basinyi, Stella (Cambridge monographs in African archaeology, 2019)
In 2008 several heritage sites in Botswana were opened for tourism in addition to the Tsodilo World Heritage Site. Insufficient research was undertaken to understand how local communities and local cultures respond to these ventures. This study presents an overview of community transformation and responses to heritage sites as globalised platforms.